Violence against women: between cultural heritage and the challenges of the new law - LAZGHED, Firouze (Social Sciences Journal)
In our study, we are exposed to the phenomenon of violence against women, a phenomenon that has recently been raised in abundance, especially with the attempt to amend the law to combat violence against women. We aim through this study to analyze the reactions resulting from the amendment of the Family Law in 2014, which resulted in two currents, one opposition and the other supportive, in order to find out the reason behind this difference, with a sociological reading of the phenomenon under study.